Trail with a bridge in the redwoods - Unknown:::Creator::::::::::::
Negative shows a bridge and trail in the redwoods. A woman is depicted standing on the right of the bridge and there is a large tree leaning over the trail. It is probably located at the YWCA's Camp Ayun Mapu in Big Basin, California.